The challenges of fatwa institutions in Malaysia in facing the progress of science and technology - Wan Mohd Khairul Firdaus, Wan Khairuldin; Daud, Ismail; Wan Nur Izzati, Wan Nor Anas; Abdul Hanis, Embong; Mohd Shukri, Hanapi (2019)
Dense technology development nowadays leads to various new issues especially in the law determination. Most of the problems have never happened before; in fact they have never been discussed in details in the books of fiqh previously. Moreover, the qualification of a mufti is usually in their main field which is in sharia studies. In encountering the problems, fatwa institution becomes the most affected body due to its role to solve the problems from the aspect of religion. Therefore, fatwa institutions in Malaysia need to take appropriate actions to get along with technology progress. This article intends to see the challenges faced by fatwa institutions in Malaysia and resolving measures executed to solve problems happening due to the technology development. This article is divided into two objectives. First, the roles of fatwa institutions in Malaysia. Second, the challenges and solutions performed by fatwa institutions to problems regarding technology. This study used documentation method to collect data. Those data then were analysed through content analysis method. The study found that there are two main institutions functioning to solve fatwa problems in Malaysia which are Department of Islamic Development Malaysia (JAKIM) and state fatwa institutions throughout Malaysia. These institutions are assisted by governmental and non-governmental bodies in ensuring the resolution of rising religious problems in Malaysia. The study also found that there are many problems faced Muslim community in Malaysia due to technology development including modern medicine, information technology and others. To handle these problems, fatwa institutions in Malaysia has done a lot of efforts to solve them according to Islamic perspective including by strengthening the methodology of contemporary fatwa research, organising fatwa discussion in group and appointing the experts of related fields.